Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7861/futurehosp.6-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Workforce: Newly graduated doctors’ experiences of conducting medical ward rounds alone: A regional cross-sectional study

Abstract: Newly graduated doctors may be expected to conduct ward rounds alone, yet studies exploring this are limited. A regional cross-sectional study was undertaken to explore foundation year 1 doctors' (FY1s) experiences of conducting ward rounds alone; all 289 FY1s on medical rotations in Yorkshire and the Humber Foundation School were invited to participate in an online survey in November 2016. Thirty-four percent (n=98) responded. The majority (62%, n=61) of respondents reported conducting the daily ward round al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The content of this edition also led me to personally reflect on my preparedness for ward rounds in week one of my medical career, and the role of the supportive staff around me who were so critical to my early professional development. The evidence presented in this journal suggests that we still have some way to go in the preparation of medical students for their 5 Although I was fortunate in that I felt at least somewhat prepared as I embarked on my medical career -and did undertake lone ward rounds twice a week -I also had a supportive team and firm structure around me, that I do not recognise in today's fragmented NHS system. I was also extremely fortunate that in my first hospital we had staff with extended roles not dissimilar to the PA (although not as comprehensive), and these staff provided both reassurance and a guiding hand, both in a practical sense (such as phlebotomy) but also in a social sense (explaining the cultural and organisational aspects of the wards and hospital to the uninitiated!).…”
Section: Reflective Practice From a Systems Perspective: Enhancing Sementioning
confidence: 95%
“…The content of this edition also led me to personally reflect on my preparedness for ward rounds in week one of my medical career, and the role of the supportive staff around me who were so critical to my early professional development. The evidence presented in this journal suggests that we still have some way to go in the preparation of medical students for their 5 Although I was fortunate in that I felt at least somewhat prepared as I embarked on my medical career -and did undertake lone ward rounds twice a week -I also had a supportive team and firm structure around me, that I do not recognise in today's fragmented NHS system. I was also extremely fortunate that in my first hospital we had staff with extended roles not dissimilar to the PA (although not as comprehensive), and these staff provided both reassurance and a guiding hand, both in a practical sense (such as phlebotomy) but also in a social sense (explaining the cultural and organisational aspects of the wards and hospital to the uninitiated!).…”
Section: Reflective Practice From a Systems Perspective: Enhancing Sementioning
confidence: 95%
“…In surveys, advanced medical students have reported a feeling of unpreparedness to manage patients safely [18][19][20][21]. According to a cross-sectional study by Pearce et al [22], the majority of Foundation Year 1 doctors in the UK performed ward rounds alone and unsupervised, and only 7% reported that they felt prepared for this task.…”
Section: Introductionmentioning
confidence: 99%